2014
DOI: 10.1039/c4ta01250j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermoelectric properties by atomic-scale percolation in digenite CuxS

Abstract: Atomic-scale percolation phenomena were found in digenite CuxS, providing a new strategy to optimize the properties of thermoelectric materials, especially for quasi disordered materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…The high impact force generated between the milling balls during the MA process and the high cooling rate after the process made the αDg structure more stable. 27 Pure Cu 1.8 S phase was obtained by sintering at T ≤ 873 K, but it was partly decomposed to Cu 1.96 S and S (volatilized) when the sintering temperature exceeded 973 K. In fact, a differential thermal analysis indicated that the decomposition starts at 817 K upon heating. 10 The decomposition is associated with sulfur volatilization, thereby lots of pores formed in the sample.…”
Section: B Digenite and Chalcocite (P-type)mentioning
confidence: 99%
See 1 more Smart Citation
“…The high impact force generated between the milling balls during the MA process and the high cooling rate after the process made the αDg structure more stable. 27 Pure Cu 1.8 S phase was obtained by sintering at T ≤ 873 K, but it was partly decomposed to Cu 1.96 S and S (volatilized) when the sintering temperature exceeded 973 K. In fact, a differential thermal analysis indicated that the decomposition starts at 817 K upon heating. 10 The decomposition is associated with sulfur volatilization, thereby lots of pores formed in the sample.…”
Section: B Digenite and Chalcocite (P-type)mentioning
confidence: 99%
“…The atomic-scale percolation phenomena of electric and thermal properties were then found in Cu 1.8±δ S, and the value of ZT was increased by 60% slightly below the percolation threshold value of δ in the conductive region. 27 Liquid-like behavior of Cu ion in the p-type Cu 2−δ S (δ = 0-0.03) affects thermal properties. 28 With increasing temperature, the heat capacity at constant pressure C p decreased clearly at T > 400 K and fell below the Dulong-Petit value at T > 800 K, leading to the reduction in κ ∝ C p .…”
Section: B Digenite and Chalcocite (P-type)mentioning
confidence: 99%
“…[6][7][8][9][10][11][12] One typical example is copper sulfides (Cu x S). [9][10][11] This family of compounds has been intensively studied in the past fifty years mainly focusing on the structural complexity and applications in solar cells. [13][14][15] In contrast, TE properties of Cu x S have been studied only very recently.…”
mentioning
confidence: 99%
“…However, the study is very fruitful and inspiring, which can assist to decide a proper composition of Cu 2− x S for an optimized thermoelectric behavior. After a long gap, recently, many research teams have reported the thermoelectric properties of copper sulfide as a function of its phases …”
Section: Strategies To Improve Thermoelectric Properties Of Copper Sumentioning
confidence: 99%